Bias-dependent transport properties of passivated tilted black phosphorene nanoribbons. Issue 16 (10th April 2018) - Subhan, Fazle; Farooq, M. Umar; Hong, Jisang
Abstract : To explore the transport properties of the passivated TPNRs, using the non-equilibrium Green's function (NEGF) technique under the DFT code. Abstract : Using the density functional theory incorporated with a non-equilibrium Green's function (NEGF) technique, we explored the bias-dependent transport of tilted phosphorene nanoribbons. Herein, we considered three types of nanoribbons: self-passivated (TPNRself ), H-passivated (TPNRH ), and O-passivated (TPNRO ) systems. The TPNRself showed an indirect band gap of 0.53 eV, whereas the TPNRH displayed a direct band gap of 1.32 eV. In TPNRO, we observed a spin-polarized band structure with a spin-dependent band gap. We found that the bias-dependent I – V curve was dependent on the passivation effect. In TPNRself and TPNRH, the current monotonically increased with an external bias, but the magnitude of the current in TPNRself was more than 10 times than that in TPNRself . Unlike the I – V characteristics in TPNRself and TPNRH, the current in TPNRO almost vanished beyond an external bias of 1.7 V. Mostly, the bias-dependent I – V was interpreted based on the band structure in the lead parts. However, we found that this conventional approach was not sufficient to analyze the I – V curve. Indeed, we showed that the detailed I – V curve could be understood by calculating the bias-dependent density of states in the scattering part related to the transmission channel. It was also found that the electron flow channel was dependent on the passivation effect and uniformly distributed over the entire nanoribbon in TPNRself and TPNRH . In contrast, the electron flowed mostly along the edge line in TPNRO . Moreover, we have found that spin polarization in the conduction current can be manipulated by an external bias, and this may suggest that the TPNRO can be utilized for potential spintronic applications.